JUDGE'S CONSIDERATION OF THE VERDICT OF JINAYAT RAPE (Study of Decision No. 5/JN.Anak/2022/MS.Tkn) - Nurhaliza, Nurhaliza; Suhartini, Suhartini (fakultas hukum universitas PGRI Semarang, 2024)
This study aims to determine how the qualification of rape against children according to Qanun Jinayat. This study also tries to explore the considerations taken by judges in determining sanctions for rape cases involving minors as stated in decision Number 5 / JN. Children/2022/MS.Tkn which discusses the crime of rape by minors. The method used in this study is normative juridical, namely legal research conducted by examining secondary data, using a statutoryÂ approach (statue approach) and a case approach.The results showed that the qualifications of rape according to Qanun Jinayat and positive law are basically the same, namely the existence of elements of coercion, violence and threats to victims that distinguish only lies in the execution, implementation and place of implementation. In addition, the judge in handing down the verdict considers the demands of the public prosecutor, defense from legal counsel, reports from the community, as well as recommendations from the child's companion or parents, without ruling out the psychological condition of the child victim.